2016
DOI: 10.1016/j.ntt.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Motor delays in MDMA (ecstasy) exposed infants persist to 2years

Abstract: Background Recreational use of 3,4 methylenedioxymethamphetamine (Ecstasy, MDMA) is increasing worldwide. Its use by pregnant women causes concern due to potentially harmful effects on the developing fetus. MDMA, an indirect monoaminergic agonist and reuptake inhibitor, affects the serotonin and dopamine systems. Preclinical studies of fetal exposure demonstrate effects on learning, motor behavior, and memory. In the first human studies, we found prenatal MDMA exposure related to poorer motor development in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
(57 reference statements)
2
23
0
Order By: Relevance
“…Consensus is that fetal exposure to alcohol is harmful. Prenatal alcohol exposure may induce abnormal brain development as well as decrease the capacity for learning and memory [12, 13]. Similar to alcohol, anticonvulsants, sedatives (such as ketamine), or narcotics can pass through the placental barrier and for ketamine in particular, researches showed its ability to impair the capacity for learning and memory [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Consensus is that fetal exposure to alcohol is harmful. Prenatal alcohol exposure may induce abnormal brain development as well as decrease the capacity for learning and memory [12, 13]. Similar to alcohol, anticonvulsants, sedatives (such as ketamine), or narcotics can pass through the placental barrier and for ketamine in particular, researches showed its ability to impair the capacity for learning and memory [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, in a longitudinal study evaluating infants, children of women using recreational drugs (ecstasy) during pregnancy, from birth to 4, 12, 18 and 24 months of age, it was shown that exposure (greater use of tablets per week) resulted in worse motor development, but without affecting mental development. These infants with more intense exposure were twice as likely to demonstrate poorer quality of motor performance than the non-exposed ones 13 .…”
Section: Resultsmentioning
confidence: 82%
“…A retrospective study of children who were pregnant with crack and cocaine during the first days of life showed abnormalities in 34.9% of the study population 14 . The changes detected were subependymal cysts in 24 children (18.6%), lentricular vascular disease in 18 children (14%), subependymal haemorrhage in 9 children (7%) and choroid plexus cysts in 9 children (7%) 13 . Dixon and Bejar 15 , in a study of full-term new-borns exposed to cocaine and methamphetamine and evaluated by cranial ultrasonography, also identified lesions such as intraventricular haemorrhage, necrosis and cavitary lesions in the basal ganglia, frontal lobes, and posterior fossa.…”
Section: Resultsmentioning
confidence: 98%
“…With the group comparisons, the more heavily MDMA-exposed neonates had significantly lower 'motor quality' scores at four months post-partum , and these psychomotor deficits remained significant at the 12-and 24-month post-partum sessions Singer et al, 2015). These findings need to be replicated, and the effects of MDMA on male sperm need to be studied.…”
Section: Neonatal Problemsmentioning
confidence: 97%